Answer :


Proof:


Take LHS:



Identities used:


cos 2x = 1 – 2 sin2 x


2 sin2 x = 1 – cos 2x



Therefore,






{ cos (π – θ) = - cos θ,


cos (π + θ) = - cos θ &


cos(2π – θ) = cos θ}





= 2


= RHS


Hence Proved


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

If a cos 2x + b sRD Sharma - Mathematics

If a cos 2x + b sRD Sharma - Mathematics

If a cos 2x + b sRD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

If <RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

If <RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

0 ≤ x ≤ π aRD Sharma - Mathematics

Prove that:RD Sharma - Mathematics